Digesting cytotoxic stressors – an unconventional mechanism to induce autophagy - Langlois, Christine R.; Wollert, Thomas (The FEBS journal, 2016)
Autophagy is an essential and fundamental pathway that clears unwanted or damaged material from the cell. Initiation of autophagy was previously shown to be dependent on the Ulk1/2 kinase complex. In this issue of The FEBS Journal, Braden and Neufeld investigated the Ulk3 homolog in Drosophila, and proposed a novel, Ulk1/2 independent pathway for autophagy initiation.